Facile preparation of high-performance Fe-doped Ce–Mn/TiO2 catalysts for the low-temperature selective catalytic reduction of NOx with NH3. Issue 77 (17th October 2017) - Xu, Quan; Su, Rigu; Cao, Li; Li, Yeqing; Yang, Chuanyao; Luo, Yan; Street, Jason; Jiao, Pengcheng; Cai, Lulu
Abstract : A Ce–Mn–Fe/TiO2 catalyst has been successfully prepared using a single impregnation method with excellent low-temperature NH3 -SCR activity. Abstract : A Ce–Mn–Fe/TiO2 catalyst has been successfully prepared using a single impregnation method, and excellent low-temperature NH3 -SCR activity was demonstrated in comparison with other typical SCR catalysts including Mn–Ce/TiO2 and metal-doped Mn–Ce/TiO2 . The crystal structure, morphology, textural properties, valence state of the metals, acidity and redox properties of the novel catalyst were investigated comprehensively by X-ray diffraction (XRD), N2 adsorption and desorption analysis, X-ray photoelectron spectroscopy (XPS), NH3 -temperature-programmed desorption (NH3 -TPD), and H2 -temperature-programmed reduction (H2 -TPR). The Fe-doped Ce–Mn/TiO2 catalyst boosted the low-temperature NH3 -SCR activity effectively under a broad temperature range (100–280 °C) with a superior NO conversion rate at low temperatures (100 °C, 96%; 120–160 °C, ∼100%). Fe doping caused this improvement by enlarging the catalyst pore volume, improving the redox properties, and increasing the amount of acidic sites. These properties enhanced the ability of the catalyst to adsorb NH3 and improved the low-temperature SCR performance, especially at temperatures lower than 150 °C. Moreover, redox cycles of Ce, Mn, and Ti (Mn 4+ + Ce 3+ ↔ Mn 3+ + Ce 4+, Mn 4+ + Ti 3+ ↔ Mn 3+ + Ti 4+ ) also played an important role in enhancing the low-temperature SCR efficiency by accelerating the electron transfer. The excellent NH3 -SCR result is promising for developing environmentally-friendly and more effective industrial catalysts in the future.